Length-Weight Relationship and Condition Factors of Some Commercial Fish from Youtefa Bay, Jayapura City, Indonesia - Ervina Indrayani; Baigo Hamuna; Lalu Panji Iman Agamawan (Jurnal Perikanan Universitas Gadjah Mada, 2023)
In this study, we used data on the length and weight of fish to determine the length-weight relationship and condition factors of eight commercial fish targeted by traditional Papuan fishers in Youtefa Bay, Papua Province, Indonesia. The fish species were Lutjanus fulvus, Gerres oyena, Parupeneus barberinus, Siganus spinus, Siganus canaliculatus, Pelates quadrilineatus. Mugil cephalus, and Hemiramphus far. A total of 245 fish specimens were collected from Papuan fishermen from January to March 2020. The total body length and weight ranged from 15.2 to 32.1 cm (average 20.26±3.73 cm) and 42.72 to 371.86 gr (average 124.10±52.45 gr), respectively. The b value ranged from 2.692 to 3.079, with the coefficient of determination (R2) ranging from 0.902 to 0.995. The growth patterns of the eight fish species were allometric (b≠3; t-test<t-tab), where L. fulvus (2.824), P. barberinus (2.914), S. canaliculatus (2.989), P. quadrilineatus (2.958), M. cephalus (2.910), and H. far (2.692) have negative allometric growth (b<3). In contrast, G. oyena (3.060) and S. spinus (3.079) have positive allometric growth (b>3). The relative condition factor and Fulton condition factor values ranged from 0.874 to 1.201 (average 0.999±0.321) and 0.204 to 2.726 (average 1.612±0.515). M. cephalus had a higher relative condition factor, while L. fulvus had a higher Fulton condition factor compared to other fish species.